Software defined vehicular networks: A comprehensive review. (6th June 2019) - Bhatia, Jitendra; Modi, Yash; Tanwar, Sudeep; Bhavsar, Madhuri
Summary: The recent breakthroughs in the automobile industries and telecommunication technologies along with the exceptional multimodal mobility services brought focus on intelligent transportation system (ITS), of which vehicular ad hoc networks (VANETs) gain much more attention. The distinctive features of software‐defined networking (SDN) leverages the vehicular networks by its state of the centralized art having a comprehensive view of the network. Its potential to bring the flexibility, programmability and other extensive advancements to vehicular networks has set the stage for a novel networking paradigm termed as software‐defined vehicular networks (SDVNs). Many researchers have demonstrated the SDN‐based VANETs with the various configuration of the SDN components in VANET architecture. However, a compilation of the work on the SDN‐based VANET system as a whole, incorporating its architecture, use‐cases, and opportunities, is still inadequate. We start with the summary of the recent studies that exist on the SDVNs, followed by the comprehensive explanation of its components. Next, we present the taxonomy of SDVN based on the architecture modes, protocols, access technologies, and opportunities with trending technologies. Finally, we highlight the challenges, open research issues, and future research directions. Abstract : This paper presents a systematic review of SDN based VANET (SDVN) by exploring its architecture, use‐cases, and opportunities. Then, introduce a summary of the recent studies exist on the SDVNs, followed by the comprehensive explanation of its components. Next, we present the taxonomy of SDVN based on the architecture modes, protocols, access technologies and opportunities with trending technologies. Finally, this paper bridges the gap between the various hybrid architectural modes and other research challenges for different use cases.